Finite Element Analysis (FEA) of blade weed design using Ansys workbench - Angger Bagus Prasetiyo; Rizqi Prastowo; Kartinasari Ayuhikmatin Sekarjati; Anita Susiana; Ichwan Noor Ardiyat; Fajar Yulianto Prabowo; Iman Pradana A. Assagaf; Jemssy Ronald Rohi; Yonathan Ito (Universitas Mercu Buana, 2022)
Manual, semi-conventional, and conventional weed eradication are the three forms of weed eradication utilized. Farmers benefit greatly from the usage of weeding equipment in combating pests in the fields. The blade you use determines how successful you are at weeding. As a result, it is required to examine the weeding weeds blade. With a tetrahedral mesh, simulation utilizing the finite element analysis approach allows for the optimization of design, computation, and prediction of material strength. The goal of this research was to figure out how much von Mises's stress, deformation, and safety factor were worth. ANSYS Workbench software was used to simulate various loadings of 10N, 25N, and 50N. The highest von Mises stress created by simulation of modelling weed blades at 10N, 25N, and 50N loads is around 2.95x10-2 MPa, 7.38x10-2 MPa, and 0.14755 MPa, respectively. Each of the safety factors is 15, and the maximum deformation value is 4.26x10-7mm; 1.06x10-6mm; 2.13x10-6mm. The safety factor indicates that the weed weeding knife design is safe to use up to 50N loading.